(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Several Iron Age/Roman images from the Northwest of the Iberian Peninsula have been related to indigenous theonyms with debatable criteria. The aim of this paper is to offer a revision of those alleged representations of vernacular deities and to re-evaluate their links with names of indigenous gods ephigraphycally attested at the current galician territory.